Vliv lidských zdrojů na úspěch mezinárodních podnikatelských aktivit: Komarativní studie v českých rodinných a nerodinných podnicích - Zapletalová, Šárka (Univerzita Pardubice, 2016)
Human resources are a significant factor facilitating the implementation of international entrepreneurial activities. Human resources are one of the most important resources, both in family and non-family businesses. People are bearers of knowledge, skills and experience. Generally, it is assumed that there is a relationship between human resources and company performance on international markets. Although the literature suggests that the link between human resources and company performance is quite positive, it is nevertheless not necessarily a direct relationship. The objective of the paper is to investigate the difference in ensuring the management of international entrepreneurial activities by human resources in Czech family businesses and in non-family businesses. The paper is based on data collected in interviews with managers and founders of Czech businesses. The businesses included in the study are those that have already undertaken internationalization activities and are incorporated in the Czech Republic. Management of international entrepreneurial activities in the Czech businesses was researched using the method of questioning: the main primary data collection instrument was a questionnaire-driven interview.
The Influence of Human Resources on the Success of International Entrepreneurial Activities: A Comparative Study in Czech Family and Non-family Busineses
Keywords: International markets; Human resources; Czech businesses; Family businesses; Non-family businesses; International entrepreneurial activities; Knowledge; Skills; Experience; F23; M16